Creating Youtube Vlog Videos Untuk Stimulasi Perkembangan Fisik Motorik Anak Usia Dini - Tisna Syafnita; Putri Ulandari (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2023)
Children's dependence on watching on YouTube currently makes their physical and motor skills do not develop optimally. we can use YouTube to make children more active in moving through the activity of Creating Youtube Vlog Videos. The type of research used is descriptive qualitative research with data collection techniques used observation, interviews and documentation. Based on the results of the research that has been done, it shows that Creating Youtube Vlog Videos activities can stimulate the physical-motor development of early childhood. Because in the process of making videos that will be uploaded on YouTube, it allows children to carry out various physical motor movements and then record them in video form. Through this activity, children become excited about doing motor-physical activities because they can watch videos of the movements they have done.